METODA PERBAIKAN TANAH LUNAK PADA RUAS JALAN SEKINCAU - SUOH DI KABUPATEN LAMPUNG BARAT - Nandang Nandang (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Cement type used at this research is PCC (Portland Composite Cement) which produced by PT.Indocement Tunggal Prakarsa Tbk. Cement is an important material as construction principalcomponent. There are many benefits that is taken from cement, as cement mixture on building,even it can be used as soil stabilization agent, especially clay. This research conducted to knowhow big swelling and swelling pressure on clay if it was added by cements on PCC. Testconducted in three phases, (1). Physical properties test of clay, and soil-cement PCC mixture, (2).Compaction test with modified proctor method; and (3). Swelling and swelling pressure test withfold loads 17,67 kg. Sample that will be tested is clay of Fila Tengah. Suwoh – West Lampung andclay that mixed cements of PCC with presentation 5%, 10%, and 15%. Base on the result, the soilof Fila Tengah, Suwoh – West Lampung is classified in soft clay category (AASHTO and Unifiedclassification). Another result obtained explain that cements of PCC usage by the certainpresentation can very affect to clay swelling and swelling pressure. The swelling of clay that wasreached is 8,75 cm. Fifteen percent cements of PCC can be pressed decreasing became 6,5 cm.The swelling pressure of clay is 120,05 kPa. Fifteen percent cements of PCC added is 70,03 kPa.Can be concluded that the best cement to clay stabilization as mixture for clay is cements of PCC.